1,000 inventions & discoveries - Bridgman, Roger, 1940- (New York : DK Pub., 2002)
Summarizes 100 notable inventions and discoveries of ancient and modern times, from 3,000,000 B.C. to the beginning of the twenty-first century A.D.
Includes bibliographical references (p 256) and index.
Keywords: Inventions -- History -- Juvenile literature; Inventions -- History; Juvenile materials